P-Hacking, P-Curves, and the PSM–Performance Relationship: Is There Evidential Value? - Dominik Vogel; Fabian Homberg (Public Administration Review, 2021)
Recent developments in the social sciences have demonstrated that we cannot uncritically aggregate the published research on a particular effect to conclude about its presence or absence. Instead, questionable research practices such as p-hacking (conducting additional analyses or collecting new data to obtain significant results) and selective publication of significant results can produce a body of published research that misleads readers even if it contains many significant results. It is, therefore, necessary to assess the evidential value of the research on a certain effect; that is, one must rule out that it is the result of questionable research practices. We introduce the p-curve method to public administration research and apply it to the research on the relationship between public service motivation (PSM) and individual performance, to demonstrate how the evidential value of a body of published research can be assessed. We find that this particular literature contains evidential value.
Keywords: 340